Pengaruh Karakteristik Pekerjaan Terhadap Budaya Organisasi Yang Dimediasi Oleh Komitmen Organisasional : Studi pada Hotel Grand Miami di Kepanjen Kabupaten Malang - Mellien Pakerti Winengku; Survival, Survival; Alfiana, Alfiana (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The purpose of this study was to determine the effect of Job Characteristics and Organizational Culture on Employee Loyalty mediated by Organizational Commitment. The population in this study were all employees of Grand Miami Hotel, totaling 55 employees. The sampling technique in this study used the Saturated Sample (Total Sampling) method, so that the entire population was used as respondents. Data were processed using Smart Partial Least Square (SmartPLS 4) software. The results showed that Job Characteristics had no significant effect on Employee Loyalty, but when mediated by Organizational Commitment, Job Characteristics had a positive and significant effect, indicating that Organizational Commitment served as a full mediator. Organizational Culture had a positive and significant effect on Employee Loyalty, both directly and indirectly through Organizational Commitment, indicating that Organizational Commitment acted as a partial mediator. In addition, Organizational Commitment was found to have a positive and significant effect on Employee Loyalty. Overall, the findings highlight the crucial role of Organizational Commitment in strengthening the influence of Job Characteristics and Organizational Culture on Employee Loyalty at Grand Miami Hotel, Kepanjen, Malang Regency.